Refleksi Kristologis yang ada dalam Berbagai Konteks - Yurin Yurin; Dorthea Aryani Wadibar; Sarmauli Sarmauli (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
Christology is a branch of Christian theology that discusses the person and work of Jesus Christ as the core of the Christian faith. The development of the modern era, characterized by globalization, pluralism, technological advancement, and cultural diversity, presents new challenges in understanding Christ in a relevant and contextual manner. This research aims to examine the development of Christological reflection in various life contexts and explain its application in contemporary life. The research uses a qualitative approach with a literature study method thru the examination of various classical and modern theological literature from both Protestant and Catholic traditions. The analysis was conducted using a historical-critical approach to understand the development of Christological thot from the early church period to the modern era. The research results show that Christology is not only doctrinal but also has practical dimensions related to personal, social, cultural, interfaith dialog, ecological, and modern challenges. Christological reflection affirms that Jesus Christ is understood as the true God and true man, serving as the foundation of spirituality, ethics, and social action for Christians. Furthermore, the contextual Christological approach helps the church present Christ's teachings relevantly in a pluralistic and dynamic society. This research implies the importance of developing contextual, inclusive, and transformative theology so that the Christian faith remains meaningful in modern life.